The HSP90 inhibitor, NVP-AUY922, sensitizes KRAS-mutant non-small cell lung cancer with intrinsic resistance to MEK inhibitor, trametinib. Issue 1 (1st March 2016) - Park, Kang-Seo; Oh, Bora; Lee, Mi-Hee; Nam, Ky-Youb; Jin, Hae Ran; Yang, Hannah; Choi, Junyoung; Kim, Sang-We; Lee, Dae Ho
Highlights: AKT activation bypasses MEK inhibition in KRAS mutant NSCLC cells with intrinsic resistance to MEK inhibition. AUY922 suppresses both PI3K-AKT-mTOR and RAF-MEK-ERK activation. AUY922 sensitizes NSCLC cells with intrinsic resistance to MEK inhibitor trametinib. Abstract: RAS-driven tumors are often difficult to treat with conventional therapies and therefore, novel treatment strategies are necessary. The present study describes a promising targeted therapeutic strategy against non-small cell lung cancer (NSCLC) harboring KRAS mutations, which has intrinsic resistance to MEK inhibition. Results showed that intrinsic resistance to MEK inhibition occurred via high AKT expression by PI3K activation as a bypass pathway. The HSP90 inhibitor AUY922 suppressed PI3K-AKT-mTOR and RAF-MEK-ERK, and rendered cells sensitive to trametinib (GSK1120212). Synergy from the combination of the two drugs was observed in only sub-therapeutic concentrations of either drug. Dual inhibition of the HSP90 and MEK signaling pathways with sub-therapeutic doses may represent a potent therapeutic strategy to treat KRAS-mutant NSCLC with intrinsic resistance to MEK inhibition and to resolve the toxicity observed upon dual inhibition of AKT and MEK at therapeutic doses in clinical trials.